5-Hydroxymethylcytosine profilings in circulating cell-free DNA as diagnostic biomarkers for DLBCL - Chen, Hangyu; Duolikun, Maimaitiyasen; Zhu, Hai-Chuan (Frontiers in Cell and Developmental Biology, 2024)
Background: 5-Hydroxymethylcytosine (5hmC) is an important DNA epigenetic modification that plays a vital role in tumorigenesis, progression and prognosis. Previous studies have shown that it plays an important role in the prognosis of diffuse large B-cell lymphoma (DLBCL) and in the prediction of the efficacy of R-CHOP therapy. However, its potential for diagnosing DLBCL has not been reported. Here, we investigated the utility of 5hmC in plasma cfDNA in the diagnosis of DLBCL.: Applying 5hmC-Seal technique, we obtained genome-wide 5hmC profiles in plasma cell-free DNA (cfDNA) samples from 176 Chinese subjects, included 86 DLBCL patients and 90 healthy controls. To investigate whether 5hmC can be used as a diagnostic biomarker for DLBCL, we separated patients and healthy controls into training (DLBCL=56, Healthy=60) and validation (DLBCL=30, Healthy=30) cohorts and developed a 5hmC-based logistic regression model from the training cohort to diagnose the DLBCL patients in the validation cohort.Results: In this study, we found 10 5hmC biomarkers, and the models created by these differentially regulated 5hmC modified genes showed high accuracy in distinguishing DLBCL patients from healthy controls (validation cohort: AUC=0.94; (95% CI 88.8% -99.4%)).Our study suggested that 5hmC markers derived from plasma cfDNA can served as effective epigenetic biomarkers for minimally invasive diagnosis of DLBCL.